Keeping One’s Distance: Translation and the Play of Possibility - Cronin, Michael (TTR)

(untitled) (Association canadienne de traductologie, 1995)
AbstractKeeping one's distance: Translation and the play of possibility – This article proposes a ludic theorisation of translation examining the implications of the concept of play for translation theory and translation pedagogy. The equation of play with a simulative mode of action points to the centrality of mechanisms of identification and projection in the translation interpreting classroom. The shift from the pre-operational to the operational level of logic and the metacommunicative and metalinguistic dimensions to play and translation demonstrate the cognitive importance of the latter, in intellectual development and the elaboration of identity. Play, metaphor and translation are linked through the concept of bisociative thinking which grounds the essential creativity of translation and its capacity for discovery. The paradoxical nature of translation and play are considered both in relation to the cognitive possibilities of translation and its contribution to aesthetic renewal. The use of a tripartite division of ludic text types in translator education and the potential of limits are further evidence for the significance of the ludic dimension to translation.